Foraging for fruits: natural resource use and its conservation potential in urban environments - Sardeshpande, Mallika (Rhodes University, Faculty of Science, Department of Environmental Science, 2020)
Wild edible fruits (WEFs) are a type of natural resource that humans across the world collect from diverse natural landscapes. They are among the most used non-timber forest products (NTFPs) and wild foods, and often serve more than a nutritional purpose for humans, in the form of fibre, fuel, medicine, and other products. The use of WEFs may augment household dietary diversity, food security, and income in some contexts. The prevalence of WEF species across the spectrum of natural to modified ecosystems presents the potential for integrated landscape-level conservation efforts centred on these species. The first half of this thesis investigates the state of knowledge about this versatile and ubiquitous resource in the wider context of other wild foods and NTFPs, and compares the patterns of use of WEFs with those of other wild foods and NTFPs. Through these studies, I find that WEFs are indeed a widely occurring, resilient, and useful resource along the rural-urban gradient. They are unique in that their use transcends the geographical and socio-economic criteria that influence the use of other wild foods and NTFPs. Based on these findings, in the second half of the thesis, I propose the use-based conservation of WEF species in urban landscapes through the practice of urban foraging. Through interviews with urban land managers and foragers, I describe the state of urban green space management and urban foraging, and identify synergies between the two. Green space management is increasingly devolved and well-defined in developed cities, and relatively diffused in smaller towns, but nevertheless supportive of use-based biodiversity conservation. Planting and foraging for WEFs in urban green spaces ties in with local and national objectives of urban land use management policy. However, the lack of information on species, spaces, and sustainability related to foraging are a hindrance to addressing this activity and harnessing its conservation potential. Foragers use a variety of WEF species collected from natural as well as highly used and urbanised areas in their cities. Although most foragers consider foraging as a cultural and recreational activity, many of them agreed with the prospect of commercialising or popularising it to protect and promote the biodiversity and culture associated with their foraging spaces. The synthesis of this study presents four possible pathways to conserve the diversity of WEF species, and to extend the benefits of WEF use to landscape stewardship. It identifies key stakeholders in implementing these pathways and possible collaborations between these stakeholders; the multiple conservation objectives and policies these pathways respond to; and context-specific considerations for policy and implementation related to planting and foraging of WEFs.
Keywords: Non-timber forest products; Wild plants, Edible; Urban plants; Urban ecology (Biology); Open spaces; Environmental protection -- Citizen participation